CYP2B6 genetic polymorphisms influence chronic obstructive pulmonary disease susceptibility in the Hainan population - Ding, Yipeng (Int J Chron Obstruct Pulmon Dis, 2019)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a lung disease closely related to exposure to exogenous substances. CYP2B6 can activate many exogenous substances, which in turn affect lung cells. The aim of this study was to assess the association of single-nucleotide polymorphisms (SNPs) in CYP2B6 with COPD risk in a Chinese Han population. MATERIALS AND METHODS: Genotypes of the five candidate SNPs in CYP2B6 were identified among 318 cases and 508 healthy controls with an Agena MassARRAY method. The association between CYP2B6 polymorphisms and COPD risk was evaluated using genetic models and haplotype analyses. RESULTS: In allele model, we observed that rs4803420 G and rs1038376 A were related to COPD risk. And rs4803420 G/T and G/T-T/T were related to a decreased COPD risk compared to GG genotype in the co-dominant and dominant models, respectively. When comparing with the AA genotype, rs1038376 A/T and A/T-T/T were associated with an increased COPD risk in the co-dominant and dominant models, respectively. Further gender stratification co-dominant and dominant models analysis showed that genotype G/T and G/T-T/T of rs4803420, and genotype A/T and A/T-T/T of rs1038376 were significantly associated with COPD risk compared to the wide type in males and females, while allele C of rs12979270 was only associated with COPD risk in females. Smoking status stratification analysis showed that rs12979270 C was significantly associated with an increased COPD risk under the allele model compared with allele A in the smoking subgroup. Haplotype analysis showed that haplotype GTA and TAA were related to COPD risk. CONCLUSION: Our data is the first to demonstrate that CYP2B6 polymorphisms may exert effects on COPD susceptibility in the Chinese Han population.